Clinical and Diagnostic Peculiarities of Immunological Adaptation in Children of the First Year of Life Suffering from Community-Acquired Pneumonia - V.S. Oleynik (Zaslavsky O.Yu., 2013)
The aim of the study was to evaluate the immunological parameters in community-acquired pneumonia in infants born with very low birth weight. A comprehensive clinical, laboratory and instrumental examination had been carried out in children of the first year of life suffering from community-acquired pneumonia who were born with very low birth weight. In the vast majority of children the clinical pattern of community-acquired pneumonia manifested with respiratory syndrome, the symptoms of respiratory distress I-II degree, intoxication and the lack of temperature response. Due to immunological examination of infants born with very low birth weight disorders in cellular and humoral immune system, as well as reduced functional capacity of phagocytes had been detected.